Germinal center responses to SARS-CoV-2 mRNA vaccines in healthy and immunocompromised individuals - Lederer, Katlyn; Bettini, Emily; Parvathaneni, Kalpana; Painter, Mark M; Agarwal, Divyansh; Lundgreen, Kendall A; Weirick, Madison; Muralidharan, Kavitha; Castaño, Diana; Goel, Rishi R; Xu, Xiaoming; Drapeau, Elizabeth M; et al. (Cell, 2022)
Vaccine-mediated immunity often relies on the generation of protective antibodies and memory B cells, which commonly stem from germinal center (GC) reactions. An in-depth comparison of the GC responses elicited by SARS-CoV-2 mRNA vaccines in healthy and immunocompromised individuals has not yet been performed due to the challenge of directly probing human lymph nodes. Herein, through a fine-needle aspiration-based approach, we profiled the immune responses to SARS-CoV-2 mRNA vaccines in lymph nodes of healthy individuals and kidney transplant recipients (KTXs). We found that, unlike healthy subjects, KTXs presented deeply blunted SARS-CoV-2-specific GC B cell responses coupled with severely hindered T follicular helper cell, SARS-CoV-2 receptor binding domain-specific memory B cell, and neutralizing antibody responses. KTXs also displayed reduced SARS-CoV-2-specific CD4 and CD8 T cell frequencies. Broadly, these data indicate impaired GC-derived immunity in immunocompromised individuals and suggest a GC origin for certain humoral and memory B cell responses following mRNA vaccination.